Accelerated Synthesis of Protected Peptides in a Continuous-Flow Fixed-Bed Reactor - Szloszár Aliz; Fülöp Ferenc; Mándity István M. (2017)
Continuous flow technologies are of considerable current interest. These methods offer several advantages over conventional batch procedures, such as faster heat and mass transfer, shorter reaction time, etc. Herein we show the development of a continuous procedure for the solid-phase synthesis of protected peptide sequences. Importantly, the synthesis of peptides is more than twice as fast as methods in the published literature. Nonetheless, the protected sequences are constructed in a highly sustainable way, because solvent usage is an order of magnitude lower than those in known literature technologies. The developed method has shown excellent sidechain protecting group tolerance with a wide range of chemical functionalities. The efficacy of the technology is demonstrated by the synthesis of various calcitonin and corticotropin fragments. Importantly, the products formed with excellent conversion and were isolated in high purity.